Ultrasound-assisted dispersive magnetic solid-phase extraction of cadmium, lead and copper ions from water and fruit juice samples using DABCO-based poly (ionic liquid) functionalized magnetic nanoparticles. (1st December 2022) - Sahebi, Hamed; Massoud Bahrololoomi Fard, Sayyed; Rahimi, Farnaz; Jannat, Behrooz; Sadeghi, Nafiseh
Highlights: DABCO-based poly (ionic liquid) functionalized magnetic nanoparticles were successfully synthesized, characterized and applied as an adsorbent. Effective parameters of UA-d -MSPE were optimized using experimental design. The measurement uncertainty was evaluated by GUM (bottom-up) approach. The method is suitable for the monitoring of trace heavy metal ions in water and fruit juice samples. Abstract: A poly (ionic liquid) (PIL) functionalized magnetic nanoparticles methodology was developed and utilized as an efficient adsorbent for the simultaneous extraction of cadmium, lead, and copper ions from water and fruit juice samples. The novel adsorbent was fabricated by grafting DABCO-based PIL onto silica-coated Fe3 O4 nanoparticles via copper (0)-mediated reversible-deactivation radical polymerization. Different techniques properly characterized the developed nanoparticles. The central composite design was used to analyze the simultaneous effects of various parameters on the extraction efficiency. The detection limits for water samples ranged between 3.2 and 9.2 ng.L -1, and fruit juice samples varied from 0.0103 to 0.1082 μg.kg −1 . The recovery ranged from 94.1 to 101.3% and 93.6 to 105.1% for water and fruit juice samples, respectively. The relive measurement uncertainty ranged from 7.7 to 13.6%. The proposed method is rapid, sensitive, environmentally friendly, and useful for monitoring the residues of heavy metal ions in water and fruit juice samples.